Updates on the Care of Cloacal Exstrophy - Claire A. Ostertag-Hill; Patrick T. Delaplain; Ted Lee; Belinda H. Dickie (MDPI AG, 2024)
Cloacal exstrophy is the most severe congenital anomaly of the exstrophy-epispadias complex and is characterized by gastrointestinal, genitourinary, neurospinal, and musculoskeletal malformations. Individualized surgical reconstruction by a multidisciplinary team is required for these complex patients. Not infrequently, patients need staged surgical procedures throughout childhood and adolescence. Following significant improvements in medical care and surgical reconstructive techniques, nearly all patients with cloacal exstrophy now survive, leading to an increased emphasis on quality of life. Increased attention is given to gender identity and the implications of reconstructive decisions. Long-term sequelae of cloacal exstrophy, including functional continence and sexual dysfunction, are recognized, and many patients require ongoing complex care into adulthood.